2001
DOI: 10.1074/jbc.m100279200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for JNK as a Stress-activated Bcl2 Kinase

Abstract: Interleukin (IL)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
205
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(214 citation statements)
references
References 49 publications
3
205
2
4
Order By: Relevance
“…Chen et al recently reported that Bcl-xl is a target gene regulated by HiF-1α (3). in addition, JnK has been shown to induce cell apoptosis by phosphorylation (and inactivation) of the anti-apoptotic proteins of the Bcl-2 family (22)(23)(24). our results therefore demonstrated that HiF-1α, which is induced under hypoxic conditions, increased the expression of Bcl-xl; thus, the hypoxic condition led to the blockage of apoptosis by inhibiting the cleavage of caspase-3.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Chen et al recently reported that Bcl-xl is a target gene regulated by HiF-1α (3). in addition, JnK has been shown to induce cell apoptosis by phosphorylation (and inactivation) of the anti-apoptotic proteins of the Bcl-2 family (22)(23)(24). our results therefore demonstrated that HiF-1α, which is induced under hypoxic conditions, increased the expression of Bcl-xl; thus, the hypoxic condition led to the blockage of apoptosis by inhibiting the cleavage of caspase-3.…”
Section: Discussionsupporting
confidence: 55%
“…BPs also cause apoptosis and activate the MaPK and c-Jun n-terminal kinase (JnK) signaling pathways in osteoclasts and J774 macrophages in vitro (19). Various studies have shown that JnK induces cell apoptosis by phosphorylation and activation of the transcription factor p53 (20,21) or by phosphorylation (and inactivation) of the anti-apoptotic proteins of the Bcl-2 family (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Bcl-2 survival proteins are known to be inhibited by JNK. [58][59][60][61] In the case of Bcl-2 and Mcl-1, JNK inactivates these survival factors by direct phosphorylation. 24,62 However, ZBP-89 expression had no effect on Bcl-2.…”
Section: Ibmentioning
confidence: 99%
“…JNK phosphorylates members of the Bcl-2 family of proteins, such as Bcl-2 and Bcl-x L , and inactivates their antiapoptotic function. [20][21][22][23][24] Moreover, the ectopic expression of constitutively active JNK (using the MKK7-JNK1 fusion protein) efficiently induces apoptosis in wild-type cells, but not cells lacking the proapoptotic Bcl-2 family members, Bax and Bak, which are essential for the mitochondria-dependent apoptotic pathway. 25 Furthermore, JNK activates proapoptotic members of the Bcl-2 family, Bim and Bmf, resulting in activation of Bax and Bak.…”
Section: Introductionmentioning
confidence: 99%